An absolute risk-guided approach to cardiovascular risk management within a chest pain clinic: the ARCPAC randomized trial. (25th November 2020) - Black, J.A; Campbell, J; Sharman, J; Nelson, M; Parker, S; Hamilton, G; Marwick, T
Abstract: Background: The majority of patients attending chest pain clinics are found not to have a cardiac cause of their symptoms, but have a high burden of cardiovascular risk factors that may be opportunistically addressed. Absolute risk calculators are recommended to guide risk factor management, although it is uncertain to what extent these calculations may assist with patient engagement in risk factor modification. Purpose: We sought to determine the usefulness of a proactive, absolute risk-based approach, to guide opportunistic cardiovascular risk factor management within a chest pain clinic. Methods: This was a prospective, open-label, blinded-endpoint study in 192 enhanced risk (estimated 5-year risk ≥8%, based on Australian Absolute Risk Calculator) patients presenting to a tertiary hospital chest pain clinic. Patients were randomized to best practice usual care, or intervention with development of a proactive cardiovascular risk management strategy framed around a discussion of the individual's absolute risk. Patients found to have a cardiac cause of symptoms were excluded as they constitute a secondary prevention population. Primary outcome was 5-year absolute cardiovascular risk score at minimum 12 months follow up. Secondary outcomes were individual modifiable risk factors (lipid profile, blood pressure, smoking status). Results: 192 people entered the study; 100 in the intervention arm and 92 in usual care. There was no statistical difference between the two groups' baseline sociodemographic and clinical variables. The intervention group showed greater reduction in 5-year absolute risk scores (difference −2.77; p<0.001), and more favourable individual risk factors, although only smoking status and LDL cholesterol reached statistical significance (table). Conclusion: An absolute risk-guided proactive risk factor management strategy employed opportunistically in a chest pain clinic significantly improves 5-year cardiovascular risk scores. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Tasmanian Community Fund